A Uniqueness Theorem for Bessel Operator from Interior Spectral Data. (30th April 2013) - Sat, Murat; Panakhov, Etibar S.
Abstract : Inverse problem for the Bessel operator is studied. A set of values of eigenfunctions at some internal point and parts of two spectra are taken as data. Uniqueness theorems are obtained. The approach that was used in investigation of problems with partially known potential is employed.